An Alliance for Accelerated Change Food system solutions at the nexus of agriculture, environment and nutrition - Alliance of Bioversity International and CIAT (Bioversity International and the International Center for Tropical Agriculture, 2020)
Our planet faces four interconnected global crises: climate change, biodiversity loss, environmental degradation and malnutrition. Food systems are both a significant driver of these crises and a victim. Food systems can, and must, be part of the solution.